2009 IEEE/RSJ International Conference on Intelligent Robots and Systems 2009
DOI: 10.1109/iros.2009.5354169
|View full text |Cite
|
Sign up to set email alerts
|

Real-time social touch gesture recognition for sensate robots

Abstract: Abstract-This paper describes the hardware and algorithms for a realtime social touch gesture recognition system. Early experiments involve a Sensate Bear test-rig with full body touch sensing, sensor visualization and gesture recognition capabilities. Algorithms are based on real humans interacting with a plush bear. In developing a preliminary gesture library with thirteen Symbolic Gestures and eight Touch Subtypes, we have taken the first steps toward a Robotic Touch API, showing that the Huggable robot beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 12 publications
(17 reference statements)
1
31
0
Order By: Relevance
“…Although most robot pets such as Paro (Wada and Shibata, 2007), AIBO (Fujita, 2001), Probo (Saldien et al, 2010), Hasbro's companion pets, 1 and JustoCat 2 are equipped with some touch sensors, for a more natural interaction animallike robots should be able to automatically understand and respond to different types of touch and interpret those touches within context. In an effort to advance the automatic understanding of social touch for robots, research has been conducted on the recognition of touch gestures (e.g., stroke, pat, and tickle), emotions (e.g., happiness, fear, and sadness), and social messages (e.g., greeting, attentiongetting, and showing affection) from pressure sensor data (Knight et al, 2009;Silvera-Tawil et al, 2012Altun and MacLean, 2015;Jung et al, 2015Jung et al, , 2016.…”
Section: Touch Interaction With Animallike Robot Companionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most robot pets such as Paro (Wada and Shibata, 2007), AIBO (Fujita, 2001), Probo (Saldien et al, 2010), Hasbro's companion pets, 1 and JustoCat 2 are equipped with some touch sensors, for a more natural interaction animallike robots should be able to automatically understand and respond to different types of touch and interpret those touches within context. In an effort to advance the automatic understanding of social touch for robots, research has been conducted on the recognition of touch gestures (e.g., stroke, pat, and tickle), emotions (e.g., happiness, fear, and sadness), and social messages (e.g., greeting, attentiongetting, and showing affection) from pressure sensor data (Knight et al, 2009;Silvera-Tawil et al, 2012Altun and MacLean, 2015;Jung et al, 2015Jung et al, , 2016.…”
Section: Touch Interaction With Animallike Robot Companionsmentioning
confidence: 99%
“…For instance, the Huggable robotic teddy bear has its own full-body somatosensory system to sense and process human touch (Stiehl et al, 2005;Knight et al, 2009). Another example is the Haptic Creature that is a zoomorphic lap pet that can sense human touch all over its body and expresses itself by purring, simulated breathing, and stiffening of the ears (Yohanan and MacLean, 2012;Altun and MacLean, 2015;Sefidgar et al, 2016).…”
Section: Touch Interaction With Animallike Robot Companionsmentioning
confidence: 99%
“…[5]). Some studies focused on the location of the touch rather than the touch gesture, such as distinguishing between 'head-pat' and 'foot-rub' [27]. While information on body location can enhance touch recognition, Silvera-Tawil et al showed that comparable accuracies can be achieved by limiting the touch location to a single arm [32].…”
Section: Touch Recognitionmentioning
confidence: 99%
“…'Normal' was defined as: the default/ regular (7), without thinking (4) and neutral (3). (32) 172 (77) 100 (33) 126 (45) 95 (27) 188 (99) 131 (45) 106 (28) 95 (30) 286 (180) 116 (35) 92 (30) 96 (26) Max pressure 1774 (919) 1643 (854) …”
Section: Self Reportsmentioning
confidence: 99%
See 1 more Smart Citation